UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK SUB TEMA PENGARUH PERUBAHAN CUACA TERHADAP KEHIDUPAN MANUSIA MENGGUNAKAN METODE THE LEARNING CELL DI KELAS III A SDN BULU LOR SEMARANG - Hastuti, Puji (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
The thematic learning process in class III A Bulu Lor, North Semarang District has so far been carried out using the lecture, dictation and question and answer method so that students only receive material passively, and the teacher is more active, judging from classical completeness as long as using conventional methods only around 48% of 34 students. To overcome this, one of the appropriate learning methods applied to realize active learning is the learning cell method. This study is intended to answer the following problems: 1) How is the application of the learning cell method in the thematic learning of the sub-theme of the effect of weather changes on human life in class III A SDN Bulu Lor, North Semarang District, for the 2019/2020 academic year?. 2) Is there an increase in learning outcomes in the thematic learning of the sub-theme of the effect of weather changes on human life in class III A SDN Bulu Lor North Semarang District in the 2019/2020 academic year after applying the learning cell method?. These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that: 1) The application of the learning cell method in the thematic learning of the sub-theme of the influence of weather changes on human life in class III A SDN Bulu Lor, North Semarang District, for the 2019/2020 academic year, made students active in the learning process by complementing each other's answers. which initially only listened and answered questions from the teacher, the student's learning cell method has become the subject of learning while the teacher only serves as a motivator who provides encouragement and guidance to students in order to achieve maximum learning outcomes 2) There is an increase in learning outcomes in thematic learning sub-themes influence weather changes on human life in class III A SDN Bulu Lor North Semarang District in the 2019/2020 academic year after applying the learning cell method, this can be seen from the increase in learning outcomes per cycle where in the pre-cycle students who complete there are 13 students or 46.43% cycle I there are 19 students a tau 67.9%, and in the second cycle there were 25 students or 89.3%. These results indicate that the results are in accordance with the indicators determined by KKM 70 to get 80% results. Likewise with the active learning, which increased in the first cycle there were 16 students or 57.1%, and in the second cycle there were 26 students or 92.9%. These results are in accordance with the indicators, namely the active category once and 80% active.